Energetic content of fish reservoirs of Manso River: spatial variations and trophic group - DOI: 10.4025/actascibiolsci.v27i4.1273 - Santana, Ana Rute Amadeu (2008)
Aiming to establish the caloric content and spatial differentiation of trophic groups present in Manso River, Mato Grosso State, the species Leporinus friderici (omnivorous), Acestrochynchus pantaneiro (piscivorous) and Schizodon borellii (herbivorous) were selected. The samples were accomplished from December/2002 to April/2004. The muscle samples were extracted from the region next to the dorsal fin, then rinsed in distillated water, and dried in a 60oC temperature. Subsequently, they were macerated and burned in calorimetric pump (Parr 1261). Although the results presented decreasing caloric values from the herbivorous to piscivorous species, they did not presented significant differences. The highest values of energy were observed on the bays. Male of A. pantaneiro presented caloric values higher than females. For this species, the samples collected in the reservoirs had the lowest caloric values and the highest amplitude of variation. In conclusion, the energetic content of these fishes can vary according to biotope and samples characteristics